The influence of the exposure to English on the language proficiency of std. 7 Afrikaans-speaking pupils : an investigation into the situation of a particular region of the Northern Cape - Kotze, G. J.(Gert Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1982.